The Potentials and Guidelines for the Development of Agricultural Tourism Attraction in Khlong Khwaeng Klan Community, Bang Toei Subdistrict, Mueang District, Chachoengsao Province - Apinya Saengsanguan; Duangkamol Panrostip Thunmatiwat; Somsak Khuhasawanwatch (My University, 2023)
The purpose of this study was to investigate the context, potential, and possibilities for the development of Agro-tourism in Klong Kwaeng Klan community, Chachoengsao province. A participatory research approach involved community leaders, tourist attraction caretakers, and community representatives as participants. The data was collected through the community platform, focus group discussions, and strategic management techniques such as Swot and Tows analyses. The results revealed that the Klong Kwaeng Klan community has a potential for Agro-tourism because of its natural beauty, distinctive communal lifestyle, varieties of practical activities in which the tourist can participate and gain knowledge whilst enjoying the nature. It is also convenient for traveling because the place is very close to Bangkok and its perimeter. Security and the enthusiasm of the community's people are the strengths that attract tourists. The community applied the following strategies as guidance for the early stages of agro-tourism development. The strategies include SO strategy by developing tourism routes connecting with other locations, WO strategy by learning from successful agricultural tourism and applying the knowledge for the community, and ST strategy by developing and making its own brands to be more widely recognized, in tandem with WT strategy. In addition, collaboration with local agencies to boost public relations in spreading interesting information about community attractions to tourists is also promoted.
Keywords: SWOT Analysis; Community Development; Local Community; Diverse Aspects of Tourism Research